2004
DOI: 10.1530/eje.0.1510383
|View full text |Cite
|
Sign up to set email alerts
|

RGS 2 expression is regulated by TSH and inhibits TSH receptor signaling

Abstract: Objective: A new family of guanosine triphosphatase-activating proteins known as regulators of G protein signaling (RGS) has been found to regulate the desensitization of several G protein-coupled ligandinduced processes. The expression of nine RGS mRNAs was found in human thyroid tissue (RGS 2,3,5,6,9,10,12, 14 and 16). At present, little is known as to whether any of the RGS proteins play a role in TSH signaling. Design and methods: To explore the involvement of RGS proteins in the regulation of TSH receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…A more detailed analysis of the lists of regulated genes (Tables 2-4) confirms previous work on thyroid cells or other cells treated with TSH-or cAMP-enhancing agents for the genes RGS2 (21,22), RGS16 (23), PDE4 (24,25), DIO2 (26)(27)(28), JUNB (19,29), NR4A1 (30), cAMP response element modulator (CREM) (31), TGF␤ (32), IL8 (33), RRAD (34), and EGR1 (19,29).…”
Section: Validation Of Microarray Datasupporting
confidence: 81%
“…A more detailed analysis of the lists of regulated genes (Tables 2-4) confirms previous work on thyroid cells or other cells treated with TSH-or cAMP-enhancing agents for the genes RGS2 (21,22), RGS16 (23), PDE4 (24,25), DIO2 (26)(27)(28), JUNB (19,29), NR4A1 (30), cAMP response element modulator (CREM) (31), TGF␤ (32), IL8 (33), RRAD (34), and EGR1 (19,29).…”
Section: Validation Of Microarray Datasupporting
confidence: 81%
“…Although a single agonist may upregulate more than one RGS, the GPCR-mediated increase in RGS gene expression is nevertheless selective. For example, the expression of RGS2 but not that of RGS3, 5, 6, 9 10, 12, 14 and 16 was found to be upregulated by the thyroid-stimulating hormone (TSH) in primary thyroid cultures [147]. This suggests that individual RGSs are upregulated to carry out specific functions.…”
Section: Induction Of Rgss By Gpcr Stimulation: Feedback Inhibition Omentioning
confidence: 99%
“…In the present study, there was no significant correlation between TSHR expression and thyroid hormone levels before initial ATD treatment, but there was an inverse correlation between TSHR expression and thyroid hormone levels after ATD treatment. Eszlinger et al [28] reported that regulators of G-protein signaling 2 (RGS2) inhibit signal transduction by TSHR. It may also have affected TSHR mRNA expression in the present study.…”
Section: Discussionmentioning
confidence: 99%